CCQM-K55.b (Aldrin) : Final report: october 2012. CCQM-K55.b key comparison on the characterization of organic substances for chemical purity - Westwood, S. (2012)
Under the auspices of the Organic Analysis Working Group (OAWG) of the Comité Consultatif pour la Quantité de Matière (CCQM) a key comparison, CCQM K55.b, was coordinated by the Bureau International des Poids et Mesures (BIPM) in 2010/2011. Nineteen national measurement institutes and the BIPM participated. Participants were required to assign the mass fraction of aldrin present as the main component in the comparison sample for CCQM-K55.b which consisted of technical grade aldrin obtained from the National Measurement Institute Australia that had been subject to serial recrystallization and drying prior to sub-division into the units supplied for the comparison. Aldrin was selected to be representative of the performance of a laboratory's measurement capability for the purity assignment of organic compounds of medium structural complexity [molar mass range 300 Da to 500 Da] and low polarity (pKOW < −2) for which related structure impurities can be quantified by capillary gas phase chromatography (GC). The key comparison reference value (KCRV) for the aldrin content of the material was 950.8 mg/g with a combined standard uncertainty of 0.85 mg/g. The KCRV was assigned by combination of KCRVs assigned by consensus from participant results for each orthogonal impurity class. The relative expanded uncertainties reported by laboratories having results consistent with the KCRV ranged from 0.3% to 0.6% using a mass balance approach and 0.5% to 1% using a qNMR method. The major analytical challenge posed by the material proved to be the detection and quantification of a significant amount of oligomeric organic material within the sample and most participants relying on a mass balance approach displayed a positive bias relative to the KCRV (overestimation of aldrin content) in excess of 10 mg/g due to not having adequate procedures in place to detect and quantify the non-volatile content—specifically the non-volatile organics content—of the comparison sample. There was in general excellent agreement between participants in the identification and the quantification of the total and individual related structure impurities, water content and the residual solvent content of the sample. The comparison demonstrated the utility of 1H NMR as an independent method for quantitative analysis of high purity compounds. In discussion of the participant results it was noted that while several had access to qNMR estimates for the aldrin content that were inconsistent with their mass balance determination they decided to accept the mass balance result and assumed a hidden bias in their NMR data. By contrast, laboratories that placed greater confidence in their qNMR result were able to resolve the discrepancy through additional studies that provided evidence of the presence of non-volatile organic impurity at the requisite level to bring their mass balance and qNMR estimates into agreement.